Fungal Toxins and Host Immune Responses - Brown, Rhys; Priest, Emily; Naglik, Julian R.; Richardson, Jonathan P. (Frontiers in Microbiology, 2021)
Fungi are ubiquitous organisms that thrive in diverse natural environments including soils, plants, animals and the human body. In response to warmth, humidity and moisture, certain fungi which grow on crops and harvested foodstuffs can produce mycotoxins; secondary metabolites which when ingested have a deleterious impact on health. Ongoing research indicates that some mycotoxins and, more recently, peptide toxins are also produced during active fungal infection in humans and experimental models. A combination of innate and adaptive immune recognition allows the host to eliminate invading pathogens from the body. However, imbalances in immune homeostasis often facilitate microbial infection. Despite the wide-ranging effects of fungal toxins on health, our understanding of toxin-mediated modulation of immune responses is incomplete. This review will explore the current understanding of fungal toxins and how they contribute to the modulation of host immunity.